Analisis Faktor Pembentuk Urban Heat Island di Kota Bitung - Elroi Lempoy; Veronica Kumurur; Fela Warouw (Sabua : Jurnal Lingkungan Binaan dan Arsitektur, 2021)
Urban Heat Island (UHI) is a phenomenon where urban areas experience hotter temperatures than the surrounding rural areas. Changes in land cover that occur include the establishment of buildings and infrastructure that replace open areas and vegetation, where the land cover that was originally permeable and moist has changed to impermeable and dry as a result of urban development which led to the formation of the Urban Heat Island. UHI is formed by various factors such as weather, geographic location, vegetation, materials, geometry and anthropogenic heat. Bitung city experienced population growth from 2008-2017 of 2.12% per year as well as various land use changes resulting in decreased open space and vegetation which led to an increase in surface temperature. Therefore this research was conducted to identify the distribution of surface temperature in the Bitung city and its forming factors. This study aims to find out how the surface temperature in the city of Bitung and the conditions of land use, building materials and urban geometry at high surface temperatures. The data analysis used is in the form of spatial analysis with GIS software in the form of ArcGIS 10.3. In determining the surface temperature, data from Landsat 8 imagery is used. From image processing in Bitung city, it was found that the lowest surface temperature was 15.47 ºC and the highest surface temperature was 43.34 ºC. The highest average surface temperature in the city of Bitung is in the sub-districts of Girian, Madidir, and Maesa with land use for housing, trade, industry and services; with the use of zinc roofing material and concrete walls and a building distance of 0.82m to 8.47m. Keyword: Urban heat island; Land use; Building materials; Urban geometry